2022
DOI: 10.1111/nmo.14367
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and clinical outcomes after dietary treatment for eosinophilic esophagitis: a prospective study

Abstract: Background: Eosinophilic esophagitis (EoE) is an allergen-mediated disease and elimination diets have proven to be effective to obtain clinical and histological remission.However, the effect of elimination diets on specific EoE transcripts and their clinical correlates is relatively unknown. The main aim of the study was to evaluate the effect of dietary treatment (four-food elimination diet [FFED]) with or without addition of amino acid-based formula (AAF) on a variety of pro-/anti-inflammatory, epithelial/ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…2C) is in line with a study measuring IL10 transcripts in EoE biopsies after a four-food elimination diet. 52 Earlier work showed that IL10 and IGHG4 expression correlated in pediatric EoE and were in turn related to histologic variables. 26 In contrast, we did not observe a relationship between the frequencies of IL-10 + and IgG4 + cells in baseline or follow-up biopsies, and only IL-10 + cells correlated with PEC or EoEHSS determinations (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2C) is in line with a study measuring IL10 transcripts in EoE biopsies after a four-food elimination diet. 52 Earlier work showed that IL10 and IGHG4 expression correlated in pediatric EoE and were in turn related to histologic variables. 26 In contrast, we did not observe a relationship between the frequencies of IL-10 + and IgG4 + cells in baseline or follow-up biopsies, and only IL-10 + cells correlated with PEC or EoEHSS determinations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…53 Thus, a higher prevalence of IL-10-expressing cells could be associated with an EoE phenotype that responds more promptly to elimination diets, as hinted at in a study showing that esophageal IL10 expression associated with a "food impaction" phenotype, whereas genes responsible for barrier integrity were dysregulated in a fibrotic, more refractory phenotype. 52 The contribution of IL-10 to disease activity is suggested in studies linking EoE histopathology to the accumulation of IgG4, an antibody class whose switch is promoted by this cytokine. 33 IGHE and IGHG4 germline transcripts, indicia of IgE and IgG4 switching, have been documented in the esophageal mucosa of EoE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, using different experimental approaches, tried to describe the potential involvement of TGF-β1 in the fibrous remodeling that happens in EoE [1] (Table 1). Used strategies ranged from esophageal epithelial cell cultures [104] to murine experimental models of EoE [105,106], while most evaluated biopsies were obtained from EoE patients [103,[107][108][109][110][111][112][113][114][115][116]. Tissue results from human EoE were also applied to a murine model [25], and blood samples were exceptionally used [117].…”
Section: Contribution Of Tgf-β1 To Fibrosis In Eoe: Distinct Methods ...mentioning
confidence: 99%
“…The approach to determine TGF-β1 also varied from one study to another. Some of them attempted to demonstrate the protein mainly by staining TGF-β1-positive cells with immunohistochemistry (IHC) [103,105,108,111,112,114] or immunofluorescence (IF) staining [107,109], while others used ELISA [104,117] or measured the changes in TGF-β1 gene expression in EoE biopsies compared to controls [108][109][110][112][113][114][115][116][117] and the changes after therapy [103,110,111]. As demonstrated, the results of these different approaches have not always been comparable (Table 1).…”
Section: Contribution Of Tgf-β1 To Fibrosis In Eoe: Distinct Methods ...mentioning
confidence: 99%